Exploring perception of social workers of the utilisation of employee assistance programme services in Greater Giyani Municipality, Limpopo Province - Makhubele, Tlangeleni Glory (My University, 2022)
Social workers are working with vulnerable, marginalised and abused clients on a daily basis. Hence, Employee Assistance Programme services are vital to nurture the emotional well-being of employees. The purpose of this study was to investigate the perceptions of social workers regarding utilisation of Employee Assistance Programme services in the Greater Giyani Municipality of Limpopo Province. The objectives of the study were to determine social workers' awareness of Employee Assistance Programme services available to them and to establish factors that contribute to the utilisation of Employee Assistance Programme services. The study adopted a qualitative approach and used face-to-face interviews aided by a semi-structured interview schedule to collect data. Non-probability sampling and purposive sample technique were used to select the participants. Moreover, exploratory design was used as a blue print of the study to obtain insight about the perception of social workers of the utilisation of Employee Assistance Programme services. The researcher used thematic analysis to analyse and interpret data. The findings show that participants are not taking advantage of the available psychosocial services within the Department of Social Development. The study also found that participants had never used the EAP, despite the fact that the majority of them had felt the need to seek professional help at some point. Furthermore, participants do not believe in the credibility of the Employee Assistance Programme resulting in them not utilising the available services. Participants expressed concerns about confidentiality, a lack of office space, resources, and poor marketing. The study has concluded that social workers based at the Greater Giyani Municipality of Limpopo Province, have a negative perception regarding the use of EAP services, hence the programme is under-utilised.
Thesis (M.A. (Social Work)) -- University of Limpopo, 2022
Keywords: Employee Assistance Programme; Perceptions; Utilisation; Social workers; Employee assistance programs -- South Africa -- Limpopo; Social workers -- South Africa -- Limpopo; Employees -- Counseling of